LEVELS OF FRESHNESS AND PHYSICAL DAMAGE IDENTIFICATION OF FISH AVAILABLE FOR COMSUMERS AT PASAR MINGGU MARKET BENGKULU - Novia Lestari; Yuwana Yuwana; Zulman Efendi (BPFP Faperta UNIB, 2015)
The purpose of this research was to identify level of freshness of some fishes available at Pasar Minggu Market in Bengkulu City based on SNI 01-2729.1-2006. The research was done by observing the available Sarden (Sadinella spp), Tuna (Thunnus spp), Tongkol (Euthynnus pelamial), Bawal Putih (Pampus argenteus) and Kakap Merah (Lutjanus malabaricus) in the morning (07.00 am), noon (12.00 am) and evening (17.00 am) for their freshness during September to Oktober 2013. Result of the research indicated that all of the observed fishes were fresh in the morning; only Sarden became unfresh at noon, and all of the observed fish has turned to unfresh anymore in the evening. Types of physical damage for Sarden was that its stomach was out and its head was off, for Tuna and Tongkol were bruish, injury, and material in the body of fish; for Bawal and Kakap were bruish and injury.